Electronic screen device usage and screen time among preschool-attending children in a suburban area of Sri Lanka - Asanka Rathnasiri; Harsha Rathnayaka; Nirmani Yasara; Sachith Mettananda (BMC, 2022)
Abstract Background Excessive use of screen devices and screen time are increasing health problems in children. We aim to describe the electronic screen device usage and determine the factors associated with their use among preschool-attending children in a suburban population in Sri Lanka. Methods A cross-sectional study was conducted in a suburban Medical Officer of Health area of Sri Lanka from January to March 2020. All children aged between 36-59 months attending ten randomly selected preschools were recruited. Data were collected using a parent-administered questionnaire and analysed using binary logistic regression in SPSS. The prevalence of electronic device usage, the average time spent on each device, and factors associated with individual device usage were analysed. Results A total of 340 children (Male-48%; mean age-50.1 ± 6.9 months) were recruited. Electronic devices were used by 96% of children. The most common devices were the television (87%) and the smartphone (63%). Of the children who used electronic devices, 60% exceeded the recommended screen time limit of one hour per day, 21% used devices for more than two hours per day, and 51% commenced using devices by two years of age. The higher education level of the father was independently associated with the use of smartphones and laptops and daily screen time of more than one hour (p < 0.05 for all). Male sex and being the only child were significantly associated with the use of smartphones, whereas maternal employment was associated with the use of laptops (p < 0.05 for all). Conclusions Electronic screen devices were used by 96% of preschool-attending children, and over 60% used them for more than the recommended daily upper limit of one hour. Higher paternal education, maternal employment and being the only child were significantly associated with electronic screen device use.